The Effect of Modification of Throwing and Catching Games on Gross Motor Skills in Children of Dharma Wanita Balongbendo Kindergarten - Ahmad, Nurdian; Kiswanto, Eric Nur; Basuki, Basuki (JOURNAL RESPECS (Research Physical Education and Sports), 2024)
Game modification is a specialised version of the game in which some rules are adapted to the needs and abilities of the players. Not only that but the equipment for in-game activities has also been adjusted. There are many kinds of modifications, one of which is the modification of leper catch. In throwing catch for kindergarten, children really need gross motor skills; there are several elements in gross motor skills, namely coordination, balance, agility, agility, and speed. This study aimed to determine the effect of playing a throwing catch on the gross motor skills of class B children at Dharma Wanita Sumokembangsri Balongbendo Kindergarten. This type of research is quantitative; the research method uses an experimental method with a group Pretest-Posttest Design design. The sample of this research is the children of Dharma Wanita Sumokembangsri Balongbendo Kindergarten. Data analysis in this study used the T-test (a different test). The results of the Paired Sample T-test show that the game of throwing catch shows a significance value of 0.00, that the value is less than alpha (0.05), and can be said H0 rejected. Thus, from the results of the data analysis, it is stated that sig>alpha or it can be interpreted that there is a significant difference in influence between the pre-test and post-test. In other words, game modification affects the gross motor skills of class B children at Dharma Wanita Sumokembangsri Balongbendo Kindergarten.